TINJAUAN TEORETIS AUDITOR INTERNAL: ETIKA PROFESI, KECERDASAN INTELEKTUAL, DAN KECERDASAN EMOSIONAL - Seran, Maria; Herwiyanti, Eliada (Universitas Katolik Indonesia Atma Jaya, 2019)
Internal auditors have an important role in helping management achieve good corporate performance and aimed at improving company performance. Internal auditors help management achieve good performance by introducing a systematic approach to evaluating and increasing the effectiveness of internal controls and providing notes on deficiencies found during evaluations. Professional ethics is a characteristic of the profession that distinguishes a profession from other professions, which functions to regulate the behavior of its members. In the audit assignment, an auditor seeks to carry out assignments in accordance with auditing standards and is guided by professional ethics. Someone who has a high IQ is expected to more easily absorb the knowledge provided so that they have a better ability to solve problems. In the world of auditor work, various problems and challenges must be faced, such as intense competition. An auditor who can solve problems in a world of work with stable emotions will produce and be able to provide better performance to the auditee. In other words, the better the emotional condition of an auditor, the more performance they will provide. Auditor performance is an action on the implementation of audit tasks that have been adjusted by the auditor in a certain period of time to achieve good work results or more prominently toward achieving organizational goals.